Corak Kritik Sastra Arab Masa Permulaan Islam Akibat Pengaruh Al-Qur’an - Qomariyah, Laili Nur; Tasnimah, Tatik Mariyatut (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
This study aims to identify the style of Arabic literary criticism due to the influence of the Qur'an, by knowing the phenomena of criticism that existed in the early days of Islam, it will be known how the frogter of Arabic literary criticism at that time. This research is a qualitative descriptive research. The data collection techniques used are reading and recording techniques, as well as collecting data related to the phenomenon of literary criticism in the early days of Islam. The purpose of this study is to determine the characteristics of Arabic literary criticism in the early days of Islam, along with aspects related to it. From the results of this study it was found that literary criticism in the early days of Islam was generally in the form of meaning criticism, namely criticism that judged the good and bad of literature in terms of meaning, this is because Arabic literary criticism was strongly influenced by the Quran, literary criticism at that time aimed to make literature in accordance with Islamic values, especially ethics. The critics in the early days of Islam were Prophet Muhammad and Omar bin Khattab. This research is expected to increase the reader's insight, and add insight to today's writers in order to know the traces of writers in the early days of IslamPenelitian ini bertujuan mengidentifikasi corak kritik sastra Arab akibat pengaruh al-Qur`an, dengan mengetahui fenomena-fenomena kritik yang ada pada masa permulaan Islam, maka akan diketahui bagaimana katakter dari kritik sastra Arab pada masa tersebut. Penelitian ini merupakan penelitian deskriptif kualitatif. Teknik pengumpulan data yang digunakan adalah teknik baca dan catat, serta mengumpulkan data yang berkaitan dengan fenomena kritik sastra pada saat permulaan Islam. Tujuan dari penelitian ini adalah untuk mengetahui karakteristik kritik sastra Arab pada masa permulaan Islam, beserta aspek yang berkaitan denganya. dari hasil penelitian ini ditemukan bahwa kritik sastra pada masa permulaan islam umumnya berbentuk kritik makna, yaitu kritik yang menilai baik buruknya sastra dari segi makna, hal tersebut dikarenakan kritik sastra Arab sangat terpengaruh oleh Al-Quran, kritik sastra pada masa tersebut bertujuan agar sastra sesuai dengan nilai-nilai Islam, khususnya budi pekerti. Adapun kritikus pada masa permulaan islam adalah Nabi Muhammad SAW dan umar bin Khattab. Penelitian ini diharapkan bisa menambah wawasan pembaca, dan menambah wawasan sastrawan era sekarang agar dapat mengetahui jejak sastrawan pada masa permulaan Islam